Munchausen Syndrome by Proxy in Singapore - Derrick Yeo; Shannon Lee (BJPsych Open, 2025)
Aims: Munchausen syndrome by proxy, or “factitious disorder imposed on another” as per DSM–V criteria, is characterised by the falsification of signs or symptoms, or induction of injury or disease, in another individual. Despite its initial description over 60 years ago, the literature on its epidemiology, management, and prognosis remains limited, with most insights derived from isolated case reports.